Ejecución presupuestaria del Gobierno Autónomo Descentralizado Parroquial Rural San Juan, perteneciente al cantón Puebloviejo del periodo 2023. - Fuentes Vera, Marylin Brillith (2024)
The budget execution in public institutions, including the Decentralized Autonomous Government of the San Juan parish in the Puebloviejo canton, faces constant challenges that affect the efficiency and effectiveness of public resource management. This study thoroughly examines the budget structure and allocation of the GAD during the 2023 period, identifying discrepancies between planned budgets and actual execution. The issue lies in the underutilization of certain items such as goods and services consumption and significant deviations in investment expenses, reflecting problems in the implementation of infrastructure projects essential for local development. The main objective is to analyze these variations to determine the level of efficiency in budget management, using a mixed methodology that includes a documentary review of budget schedules and interviews with the financial manager. The results reveal balanced execution in current expenses but notable inefficiency in investment expenses, suggesting the need to improve planning and internal control. It concludes that strengthening technical capacity and establishing precise mechanisms for revenue collection can enhance financial sustainability and the GAD's ability to meet its institutional objectives and community needs.